INTEROSPECT!!!! THE RIGHT TIME TO LOOK IN TO SELF (International Journal of Physiotherapy, 2014)
Exactly one month back we, the physical therapists all over the world celebrated world physiotherapy day on 8th of September. The theme of world confederation for physical therapy (WCPT) for the year 2014 is “FIT TO TAKE PART”, concreting the role of physical therapists in helping the people with long term illness or disabilities, to become independent and fulfill their part in the race of life. In general, any disease that is persistent and manifests its effects over time can be called a chronic illness. Non Communicable Diseases like cardio-vascular diseases, cancer, hypertension, diabetes mellitus, and other conditions like autoimmune disorders, Alzheimer’s disease, chronic pain syndromes and the list keeps going as we try to name the conditions that can be counted as a long-term disease.